Employment adjustment in German firms - Sven Jung (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2012)
Using a representative establishment data set for Germany, we show that, in line with the existing literature for several countries, firms' adjustment costs for employment are characterized by a fixed and convex functional form. Furthermore, they are asymmetric with dismissal costs exceeding hiring costs. An analysis of firms' adjustment in the period 1996-2010 also indicates that adjustment behavior has changed over time. Comparing the employment adjustment in the two observed business cycles comprising the years 1996-2003 and 2004-2010, we find that the adjustment speed was higher in the second business cycle indicating that adjustment costs have fallen in recent years. – – Anhand von repräsentativen Daten des IAB-Betriebspanels wird gezeigt, dass die Kosten der betrieblichen Beschäftigungsanpassung in Deutschland eine funktionale Form mit fixer und konvexer Komponente aufweisen, wie es auch frühere Studien für andere Länder feststellen. Des Weiteren ist die Struktur der Anpassungskosten asymmetrisch, wobei die Entlassungskosten größer als die Einstellungskosten sind. Bei der Analyse des betrieblichen Anpassungsverhalten für den Zeitraum 1996-2010 wird zudem deutlich, dass sich das Verhalten über die Zeit geändert hat. Ein Vergleich der betrieblichen Beschäftigungsanpassung in den zwei beobachteten Konjunkturzyklen 1996-2003 und 2004-2010 zeigt eine schnellere Anpassung im zweiten Konjunkturzyklus, was auf gesunkene Anpassungskosten hinweist.
Keywords: C24; D22; E24; J23; 330; adjustment costs; dynamic labor demand; employment adjustment; Germany